Effects of Agricultural Residues as Carriers for Bio-fertilizer Production to Promote Tomato Growth in Saline Soil - Pornrapee Sarin (Science Faculty of Chiang Mai University, 2019)
The detection of plant growth promoting properties of three isolates of rhizobacteria (Enterobacter aerogenes P8, Bacillus tequilensi N15, Pseudomonas azotoformans I2.1) showed positive results for nitrogen fixing, phosphate solubilization, ACC deaminase activity, cellulolytic activity and IAA production but activity declined when the concentration of NaCl in the medium was increased. Among the four types of carrier tested (rice husk ash, rice straw, sugarcane leaves and coconut coir), rice husk ash was the best carrier, able to support the highest growth and survival of rhizobacteria under the temperature range of 30 – 50 0C. The maximum number of survival rhizobacteria cells was found (109-1010 CFU g-1) on day 15 of incubation, at 30 0C. The growth of tomato plants in two different soils (normal and saline soil) showed that biomass was significantly highest with the treatment of chemical fertilizer supplemented with rhizobacteria. In normal soil, the biomass was 4.46 g pot-1, while it was 5.15 g pot-1 in saline soil. The accumulation of proline content in the tissue of tomato in the control treatment (without supplemented rhizobacteria and without supplemented with carrier in both normal and saline soil conditions) was higher than with other treatments. The highest total enzyme activity in soil samples detected by using the fluorescein diacetate hydrolysis (FDA) method was found in the treatment containing rice husk ash as carrier, supplemented with rhizobacteria in saline soil.